Effects of Pyramid Resistance Training Method on Body Composition Among Individuals Supplementing with 5 mg Creatine Monohydrate - Shodiq, Burhaan; Aryatama, Bagus; Hufadz, Muhamad Ihsan; Maghribi, Inosen Lingsir; Herbhakti, Fahrizal Akbar (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Body composition is a key indicator in assessing an individual's fitness level and health status. This study examines the effects of pyramid resistance training and 5 mg of creatine monohydrate supplementation on body composition measures, including body weight, BMI, body fat percentage, and muscle mass percentage. The population in this study consisted of males aged 20 to 25 years who actively participated in training programs at a fitness center in Region X. This research employed a quasi-experimental design with pretest and posttest measurements. Body composition was measured using bioelectrical impedance analysis (BIA). All data were analyzed in SPSS version 27.0.1.0 using paired-samples t-tests with a significance level of 0.05. The results show a statistically significant change (p < .001) in all variables after the intervention, body weight increased by an average of 1.98000 kg, BMI showed an average increase of 0.70667, body fat percentage decreased by an average of -1.87333%, and muscle mass percentage increased by an average of 1.25333%. These findings suggest that combining the pyramid resistance training method with creatine monohydrate supplementation may have a positive impact on body composition